The receptor for advanced glycation end product (RAGE) pathway in COVID-19. (17th February 2021) - Yalcin Kehribar, Demet; Cihangiroglu, Mustafa; Sehmen, Emine; Avci, Bahattin; Capraz, Aylin; Yildirim Bilgin, Ayse; Gunaydin, Caner; Ozgen, Metin
Abstract: Introduction: Coronavirus disease-2019 (COVID-19) with lung involvement frequently causes morbidity and mortality. Advanced age appears to be the most important risk factor. The receptor for advanced glycation end-product (RAGE) pathway is considered to play important roles in the physiological aging and pathogenesis of lung diseases. This study aimed to investigate the possible relationship between COVID-19 and RAGE pathway. Materials and methods: This study included 23 asymptomatic patients and 35 patients with lung involvement who were diagnosed with COVID-19 as well as 22 healthy volunteers. Lung involvement was determined using computed tomography. Serum soluble-RAGE (sRAGE) levels were determined using enzyme-linked immunosorbent assay. Results: The sRAGE levels were significantly higher in the asymptomatic group than in the control group. Age, fibrinogen, C-reactive protein, and ferritin levels were higher and the sRAGE level was lower in the patients with lung involvement than in the asymptomatic patients. Conclusions: In this study, patients with high sRAGE levels were younger and had asymptomatic COVID-19. Patients with low sRAGE levels were elderly patients with lung involvement, which indicates that the RAGE pathway plays an important role in the aggravation of COVID-19.